PENANGGALAN 14C UNTUK MENENTUKAN UMUR PELAPUKAN TANAH DENGAN METODE RADIOKARBON - Darwin A. Siregar; Satrio (BRIN, 2012)
Radiocarbon dating is a tool for age determination of a carbon sample. During the time, synthesis benzene method is used for age determination mentioned. By this method it could be analyzed one sample per day only with high material cost. Lately, it has been developed a new method, namely CO2 absorption method. The latest method is often called as direct counting CO2, because radioisotope of 14C in CO2 is counted directly and converted to age. The aim of the development and the use of the method are supporting some research in isotope hydrology, oceanography, climatology, geology, and archeology by faster, economic and practice. The result of 14C analyses for the same sample using the CO2 absorption when compared to the synthesis benzene method is relatively equal.